Frequency of Staphylococcus aureus virulence genes in milk of cows and goats with mastitis - Atzel C. Acosta; Pollyanne Raysa F. Oliveira; Laís Albuquerque; Isamara F. Silva; Elizabeth S. Medeiros; Mateus M. Costa; José Wilton Pinheiro Junior; Rinaldo A. Mota (Pesquisa Veterinária Brasileira)
ABSTRACT: The present study determined the frequency of Staphylococcus aureus virulence genes in 2,253 milk samples of cows (n=1000) and goats (n=1253) raised in three different geographical regions of the state Pernambuco, Brazil. The presence of genes of virulence factors associated to adhesion to host cells (fnbA, fnbB, clfA and clfB), toxinosis (sea, seb, sec, sed, seg, seh, sei, tsst, hla and hlb), and capsular polysaccharide (cap5 and cap8) was evaluated by PCR. A total of 123 and 27 S. aureus strains were isolated from cows’ and goats’ milk, respectively. The sec and tsst genes were detected exclusively in goats’ isolates, while the seh gene was only identified in cows’ isolates. The number of toxin genes per strain showed that goats’ isolates are likely more toxic than bovines’ isolates. The cap5 genotype predominated in both host species, especially in strains collected from cows raised in the Agreste region. The cap8 genotype is likely more virulent due to the number of virulence genes per strain. The results of the present study demonstrate that S. aureus may pose a potential threat to human health in Brazil, and, therefore, these results should support actions related to mastitis control programs.